MaqÃ¢sid al-QurâÃ¢n dan Deradikalisasi Penafsiran dalam Konteks Keindonesiaan - Fikriyati, Ulya (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
This article deals with the viewpoint that the reading of the QurâÃ¢n by a certain generation is subject to criticism by the following generation. The article seeks to offer, as an example, the deradicalization of interpreting the so-called âradicalâ verses of the QurâÃ¢n in Indonesian context. Islam in Indonesia always interact with various races, ethnicities, religions and beliefs, and therefore requires a type of exegesis different from other regions such as the Middle East. For the radicalization of interpretation, this article offers what is called the maqÃ¢sid al-QurâÃ¢n as its parameter. The maqÃ¢sid al-QurâÃ¢n consists of seven points: 1) Hifz al-dÃ®n wa tatwÃ®r wasÃ¢ilih, 2) Hifz al-nafs wa tatwÃ®ruhÃ¢, 3) Hifz al-âaql wa tatwÃ®ruh, 4) Hifz al-mÃ¢l wa tanmÃ®yat wasÃ¢ilih, 5) Hifz al-âird wa tatwÃ®r al-wasÃ¢il li al-husÃ»l âalayh, 6) TahqÃ®q al-huqÃ»q al-insÃ¢nÃ®yah wa mÃ¢ yandarij tahtahÃ¢, 7) Hifz al-âÃ¢lam wa âimÃ¢ratuhÃ¢. As spirit and parameter, the maqÃ¢sid al-QurâÃ¢n necessitates the dialectics of dynamic interpretation without any judgment of infidelity or heresy. If a certain reading of the Qurâanic verses deviates from these seven maqÃ¢sid al-QurâÃ¢n above, it deserves to be examined further, but not to be immediately suppressed.